(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
Investigation has been carried out to the flora of Chittagong University Campus from July 2021 to February 2022 to recognize the diversity of wild tree species as well as the species planted in campus area. A total of 304 tree species (both wild and planted) belonging to 201 genera under 69 families was recognized from the Chittagong University Campus flora. These species were categorized as angiosperms (297 species under 196 genera and 64 families) and gymnosperms (7 species under five genera and five families). Furthermore, the angiosperms were classified as dicot (95% species) and monocot (5% species). Among 69 families, top 10 families represented 47% of all species and remaining 59 families represented by 53% of the species. The study revealed that 12% of species were found in natural habitat, 32% in conservation programs, 20% both in natural and conservation areas, and 36% were exotics. Among 304 species, 13% were regarded as Vulnerable, 4% as Endangered and 3% as Critically Endangered, and collectively treated as threatened (20% of all recorded species). A checklist is prepared with updated nomenclature; each species is annotated with local name(s), family name, habitat, status of occurrence (wild/planted), and conservation status. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(1): 57-72